Seismic Hazard and Risk Assessment Updated Overview with Emphasis on Romania (Springer Natural Hazards,, 2018)
This book contains the best contributions presented during the 6th National Conference on Earthquake Engineering and the 2nd National Conference on Earthquake Engineering and Seismology - 6CNIS & 2CNISS, that took place on June 14-17, 2017 in Bucharest - Romania, at the Romanian Academy and Technical University of Civil Engineering of Bucharest. The book offers an updated overview of seismic hazard and risk assessment activities, with an emphasis on recent developments in Romania, a very challenging case study because of its peculiar intermediate-depth seismicity and evolutive code-compliant building stock. Moreover, the book collects input of renowned scientists and professionals from Germany, Greece, Italy, Japan, Netherlands, Portugal, Romania, Spain, Turkey and United Kingdom. The content of the book focuses on seismicity of Romania, geotechnical earthquake engineering, structural analysis and seismic design regulations, innovative solutions for seismic protection of building structures, seismic risk evaluation, resilience-based assessment of structures and management of emergency situations. The sub-chapters consist of the best papers of 6CNIS & 2CNISS selected by the International Advisory and Scientific Committees. The book is targeted at researchers and experts in seismic hazard and risk, evaluation and rehabilitation of buildings and structures, insurers and re-insurers, and decision makers in the field of emergency situations and recovery activities.